Concluding destructive investigation of a nine-year-old marine-exposed cracked concrete panel. (March 2023) - Geiker, Mette; Robuschi, Samanta; Lundgren, Karin; Paraskevoulakos, Charilaos; Gundlach, Carsten; Danner, Tobias; Jakobsen, Ulla Hjorth; Michel, Alexander
Abstract: This study undertaken on a nine-year-old cracked concrete panel further investigates the impact of cracks on the corrosion performance of conventional steel reinforcement in marine-exposed concrete to explain observed monitoring data. The present data covers seven 1.80 m long (12.6 m) reinforcing bars embedded in good quality concrete (w/b = 0.40 and cover >75 mm). Each bar was crossed by two horizontal cracks (surface crack widths 0.20–0.30 mm). The investigation showed no corrosion on the surface of the reinforcing bars, in either cracked or uncracked areas. Two of the seven reinforcing bars were instrumented in the vicinity of the cracks. Extensive corrosion was found in the interior of all instrumented parts of these bars. This may explain the monitoring data despite the lack of corrosion on the exterior surface of the two instrumented rebars. However, with no other weaknesses, the remaining conventional rebars showed no impact from the cracks. Highlights: Tapered horizontal cracks (0.2-0.3 mm) in marine concrete (w/c=0.40, >75 mm cover) Decreased crack width due to precipitation of calcite, brucite and portlandite Cracks had facilitated chloride ingress to the steel-concrete interface Corrosion was not found on rebars in any notable amounts No/limited impact of horizontal tapered cracks for large cover and Portland cement